The Signification of “Contrary Implication (Mafhūm al-Mukhālafah)” from Expression to Meaning among Islamic Jurisprudence Scholars - abdedaim, Azzddine (El Omda in Linguistics and Discourse Analysis, 2023)
This study highlights the disagreement between Hanafis and the great majority of fundamentalists over The verbal meaning in “Divergent meaning”, and Is it a authority to derivation legal rulings from texts?. The study also explains the cause of this disagreement; is the absence of the legal ruling upon the absence of a restriction derived from “Divergent meaning” or is it fixed by presumption of innocence? Because, in fact, there is no ordering before the receipt of the Divine law.